Female EFL Pre-service Teacher’s Emotional Geography in Teaching Practicum during Limited Face to Face Learning - Rizki Azizatul Ulya; Mansyur Srisudarso (Journal of Education For Sustainable Innovation, 2023)
The school environment serves as a domain of learning characterized by a diverse range of emotional complexities. The dynamics of affect that emerge within the classroom setting may give rise to heterogeneous interpretations among educators, influenced by the interactions and dynamics of proximity or distance between teachers and students. This research explores the emotional geography dimension of female prospective English language teachers in the context of conducting teaching practices during the period of limited face-to-face instruction. The narrative approach method is adopted with the intention of capturing narrative accounts concerning the affective experiences of female student teachers who are in the process of developing their careers as educators. The subjects of this study are female student teachers pursuing education as prospective educators within a state university institution in Karawang, West Java, Indonesia. The method of semi-structured interviews is implemented as a tool for collecting relevant data. The data that has been successfully collected pertains to the affective experiences of the participants while conducting teaching practices during the period of limited face-to-face instruction. Subsequently, this data is analyzed with reference to the conceptual framework of "Emotional Geography" proposed by Hargreaves (2001). This study reveals the affective experiences of female prospective teachers in the execution of teaching practices within the context of limited face-to-face instructional settings. The experiences undergone by these prospective teachers entail a multitude of emotions encompassing both positive and negative dimensions. Some of the emotions experienced encompass tension, fear, anxiety, surprise, confusion, stress, overwhelm, helplessness, empathy, relaxation, tranquility, happiness, pleasure, and gratitude.